Empowering Youth of Nagari Koto Tuo Through Population Information Systems and Digital Marketing for Household Products - Syukriadi; Amrizal; Hendra; Rabby Nazli; Ega Evinda Putri; Widya Febrina (Unram Journal of Community Service, 2025)
This community service activity aims to increase the digital literacy and entrepreneurial capacity of youths in Nagari Koto Tuo, Harau District, by introducing a Population Information System and training on Digital Marketing for household products. Through a series of workshops held at the computer laboratory of Politeknik Pertanian Negeri Payakumbuh, participants were taught basic data management, website creation, and strategies for marketing local products through digital platforms. This program provides solutions to the lack of a structured population data system and the limited market reach of household businesses. The outcomes include the development of a prototype village population database system and enhanced participant capability in online marketing.